Post‐20 ka Earthquake Scarps Along NE‐Tibet's Qilian Shan Frontal Thrust: Multi‐Millennial Return, ∼Characteristic Co‐Seismic Slip, and Geological Rupture Control. Issue 12 (29th November 2021) - Li, Zhanfei; Xu, Xiwei; Tapponnier, Paul; Chen, Guihua; Li, Kang; Luo, Jiahong; Cheng, Jia; Kang, Wenjun
Abstract: Earthquake slip distributions help constrain rupture behavior and return times. Here, by combining 0.5‐m‐resolution image and topographic data interpretation with fieldwork, we quantify the co‐seismic throw distribution and rupture geometry of the 1609 Hongyazi earthquake along the Qilian Shan Fodongmiao fontal thrust (NE Tibet). We measured 396 vertical offsets across mapped geomorphic units along the thrust trace. The 1609 rupture was ∼118‐km long, with average co‐seismic throw and slip amounts of ∼1.8 ± 1.0 and ∼2.9 ± 1.4 m, respectively, consistent with a magnitude M w of 7.4 ± 0.3. Along the ∼88‐km‐long western stretch of the thrust, our data also reveal five distinct clusters with peak cumulative throws (∼4.9, 9.3, 13.8, 18.0, and 22.2 m), implying older ruptures with nearly characteristic slip during five M w  ∼ 7.6–7.8 events, three of which were also identified in trenches. Two of these earthquakes ruptured the entire thrust, while three mainly broke the western and middle segments. The thrust geometry and segmentation are influenced by geological inheritance. The middle segment emplaces Silurian granites atop Quaternary alluvium, which may account for its irregularly cusped trace, and favor rupturing during large, M w ∼7.8 events with multi‐millennium (∼3.7 +0.5 /−2.2 ka) return times. Since ∼20 ka, the Fodongmiao Thrust has kept shortening and uplifting Tibet's northeastern boundary at steady rates of ∼1.4 and 1.1 mm/a, respectively. The remaining oblique component of convergence across the ∼800‐km‐long pushup between the Altyn Tagh and Haiyuan faults is absorbed by slip partitioning along the left‐lateral Changma and Lenglongling faults. Plain Language Summary: Co‐seismic slip measurements are essential to assess earthquake return times on active faults. Across thrusts, superficial throws help corroborate paleo‐seismological observations in shallow trenches. For ∼120‐km along Qilian Shan's Fodongmiao frontal thrust, 0.5‐m resolution UAV data and detailed geomorphic mapping capture the full distribution of co‐seismic vertical displacements (averaging ∼2 m) that resulted from the 1609 Hongyazi earthquake and five older, Mw ∼7.6–7.8 events (∼average 4.1 +0.5 /−1  m) all of which postdated the Last Glacial Maximum (∼20 ka). For the older events, the data is consistent with ∼characteristic slip (∼average 6.5 m) and multi‐millennial (∼3.7 +0.5 /−2.2 ka) return. Geological inheritance seems to have exerted control on the rupture geometry. The broad‐scale crustal deformation across Northeastern Tibet's "pushup corner" requires partitioning of the far‐field, oblique, contemporary convergence rate (∼7 mm/yr) between the left‐lateral Altyn Tagh and Haiyuan Faults (∼1 cm/yr) and 5 parallel intervening thrusts (∼1.4 mm/yr). Key Points: The average co‐seismic throw, rupture length, and Mw magnitude of the 1609 Hongyazi Earthquake were ∼1.8 ± 1.0 m, ∼118 km, and 7.4 ± 0.3, respectively Since the LGM, another five ∼ M 7.6–7.8 earthquakes broke the Fodongmiao frontal thrust, with ∼average characteristic throws of ∼4.1 +0.5 /−1.0  m The Paleozoic to Cenozoic hanging‐wall bedrock exerted strong control on the thrust geometry and surface trace complexity